Fansub and Religious Translation: Exploring the Translation Techniques for Online Da'wah Videos - Darissurayya, Vina (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
This study explores the techniques used in the audiovisual translation process of religious da’wah videos. The study used Molina and Albir translation techniques category. The study's object was three Youtube videos from Nouman Ali Khan Indonesia Channel, which focused on making subbed videos from Nouman Ali Khan Official Youtube Channel. The study discovers that the fan translators utilized varied techniques of translation. Every video at least had more than ten types of techniques, with the literal translation technique becoming the most used among all. The fansubbers also utilized other techniques to tackle the translation of Arabic data, such as omission, transliteration, and transcription. This study affirms that literal translation is a dominant technique applied for English-Indonesian translation. The Arabic data, however, comprise a small part of the finding, showing an interesting discovery as some techniques are unavailable in Molina and Albir categories. This study affirms the position of fansubber can apply different techniques of translation, although the literal translation is the most dominant one.